The European arrest warrant as an instrument of judicial cooperation: advantages and problematic aspects - Shyshatska, Y. (Український політико-правовий дискурс, 2026)
The article provides a comprehensive analysis of the European Arrest Warrant as a key instrument of judicial cooperation in criminal cases within the European Union. The prerequisites for its introduction related to the need to increase the efficiency and speed of the procedures for the transfer of persons, as well as the rejection of bulky intergovernmental extradition mechanisms, are considered. Special attention is paid to the legal nature of the warrant, its regulatory consolidation in the Framework Decision of the Council of the EU of June 13, 2002, and the implementation mechanism through the principle of mutual recognition of judicial decisions. The main features of the application of the European Arrest Warrant are analyzed, the simplification of the transfer procedures, the introduction of clear procedural deadlines, the expansion of the list of criminal offenses for which transfer is allowed, as well as the partial rejection of the principle of double criminality. The advantages of this institution compared to traditional extradition, consisting in increasing the efficiency of cross-border criminal justice and strengthening mutual trust between EU member states, are highlighted. At the same time, the problematic aspects of the practical application of the warrant are outlined. Attention is drawn to the difficulties associated with the ambiguity of information, differences in national legal systems, procedural complications of the transfer of persons, as well as the risks of human rights violations. Separately, the controversial issues regarding the restriction of states' abilities to refuse the transfer of their own citizens and potential abuses of this instrument are analysed. It is concluded that the European Arrest Warrant is an effective mechanism of criminal law cooperation, which reflects the transformation of extradition law in the direction of integration and simplification of procedures, but requires further improvement taking into account practical challenges and the need to ensure a balance between the effectiveness of justice and the guarantees of human rights.